Industry Support of Patient Advocacy Organizations: The Case for an Extension of the Sunshine Act Provisions of the Affordable Care Act - McCoy, Matthew S. (Am J Public Health, 2018)
Patient advocacy organizations (PAOs) have long been regarded as important representatives of patient and caregiver interests in health policy debates. Recently, however, PAOs have attracted increased scrutiny over their financial ties to drug and device companies. In the past year, researchers and policymakers have called for the creation of a “sunshine law” requiring mandatory public reporting of industry payments to PAOs. Others have suggested that increased transparency would do little to address, and may even exacerbate, underlying concerns about proindustry bias among industry-funded PAOs. To date, however, the benefits of a sunshine law have not been well articulated, nor have objections to the idea been carefully addressed. In particular, little attention has been paid to clarifying the merits of statutorily mandated disclosure relative to those of increased voluntary disclosure by PAOs. I examine arguments for and against a sunshine law and conclude that the balance of reasons supports the enactment of such a law.